The Rotating Roles Method as a Determinant of the Social Development of Early Age Students - Yennizar N; Novi Susanti; Fathor Rozi; Wasilatun Nofiyah; Eny Noer Ainy (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
Teachers as learning movers are often still having difficulties and are less successful in attracting students' attention to learning and freezing students' roles and social development. Some of the factors that cause the failure of students' social development include the lack of innovation and teacher competency in each lesson. This study aims to determine the form of activities that are applied by the teacher in the rotating roles method to develop students' social competence. This study uses a qualitative approach to the type of case study. This research is located in RA. Misbahul Islam Sogaan Pakuniran. Collecting data in this study used interview techniques with school principals, homeroom teachers for grades A and B, observation, and documentation. The data analysis used is data reduction, data presentation and conclusion. The results of the study mentioned RA. Misbahul Islam Sogaan Pakuniran in applying the rotating roles method was able to develop the social skills of his students effectively, such as being empathetic, sympathetic, happy, independent, cooperative, and easy to socialize with his friends. The rotating roles learning method is modified into 3 stages in practice, consisting of forming student learning formations as the opening stage, demonstrating the student's role as the core stage, and reflecting on the student's role.